Association Of Awkward Wrist Posture With Symptoms of Carpal Tunnel Syndrome In Online Motorcycle Taxi Drivers In Palembang - Islamia, Medina Putri; Adnindya, Msy Rulan; Legiran, Legiran; Laeto, Arwan Bin; Hasbi, Alfian (Faculty of Medicine, 2024)
Carpal tunnel syndrome is a musculoskeletal disorder of the wrist caused by pressure on the median nerve as it passes through the carpal tunnel, resulting in symptoms such as pain, tingling, and numbness. One of the jobs that is at risk of causing CTS complaints is online motorcycle taxi drivers because the awkward posture of the wrist while driving can increase the occurrence of CTS. This research aims to determine there is a relationship between awkward wrist posture and Carpal Tunnel Syndrome based on the Boston Carpal Tunnel Questionnaire (BCTQ) in online motorcycle taxi drivers in Palembang City. This research used a cross sectional method. The data obtained is primary data obtained from interviews using the Boston Carpal Tunnel Questionnaire (BCTQ) to see Carpal Tunnel Syndrome, and Rapid Upper Limb Assessment (RULA) to measure awkward wrist posture. There is no significant relationship between awkward wrist posture (p=0.487) age (p=0.757), length of service (p=0.928), duration of work (p=0.761) with Carpal Tunnel Syndrome based on the Boston Carpal Tunnel Questionnaire (BCTQ). While BMI has a significant relationship (p=0.043) with Carpal Tunnel Syndrome based on the Boston Carpal Tunnel Questionnaire (BCTQ). The conclusion is there is no significant relationship between awkward wrist posture and Carpal Tunnel Syndrome based on the Boston Carpal Tunnel Questionnaire (BCTQ) in online motorcycle taxi drivers in Palembang City.